An Empirical Analysis on Critical Success Factors for Enterprise Resource Planning (ERP) Implementation in Automobile Auxiliary Industries - Lakshmanan, Srinivasan; Edmund Christopher, S; Kinslin, D (International Journal of Engineering and Technology, 2018)
The aim of this study is to investigate Critical Success Factors (CSFs) for Enterprise Resource Planning (ERP) Implementation in Automobile Ancillary Industries (AAIs). Therefore. An in-depth and systematic literature review is done to find out the existing reviews of CSFs. Based on the review, several Discussions, Interviews and Benchmarking with experienced ERP consultants and Project management team with ERP implementations in AAIs. Thus, we showed that all factors found in the literature also affected the success of ERP projects in AAIs. CSFs Training and development, Top Management Support and commitment and Project Management, Advanced Hardware and Software and Change Management will optimize the business Process and improve the business performance and make success of the ERP Implementation. Friedmanâ€™s ranking analysis and correlation analysis were applied and detailed analysis were submitted on this study However, within those projects, Advanced Hardware and Software gained much more importance compared to the factors that most influence the success of ERP Implementation in AAIs, factors like Training and Development and Top Management Support and Commitment were even more important than Change Management and which were the most important factors in Success of the ERP Projects. This practical guidance will be helpful for the company owners, senior executives, managers and ERP consultants to be more proactive, efficient and better prepared for making Successful implementation of ERP with their limited resources especially in AAIs.Â Â